Redescription of the tadpole of Kaloula taprobanica (Anura: Microhylidae)from Sri Lanka - Wewelwala, Krishan; Alagiyawadu, Anoma I.; Kodituwakku, Gayanthi K.; Bopage, Malaka M. (Zootaxa, 2013)
According to Frost (2013), the genus Kaloula currently contains 15 species. It has a wide distribution ranging from Korea, northern China to lesser Sundas and Philippines; Bangladesh, India, and Sri Lanka; controversially in Nepal (Frost, 2013). So far, only one species is recorded from Sri Lanka, namely Kaloula taprobanica as originally described by Parker (1934). During a recent field trip, we found a large amount of tadpoles of this species in the environments of the city of Galle, Southern province, of Sri Lanka. Tadpoles were collected from 26/November/2010 up to 01/January/2011, from a rainwater dripped pond in a human settlement (06°03’29.7” N, 80°12’19.5” E, 17 m above sea level) and 18 calling males were observed in this pond. In the same pond also Polypedates cruciger (Blyth, 1852) was present. After the mating of K. taprobanica, large numbers of eggs were observed (n=1300). This water body was situated in an open area and the maximum depth of the pond was about 2.5 m. At the time of collection, the tadpoles were in different Gosner (1960) stages. Live specimens reared through metamorphosis (n=9) were used for the identification, and identification was based on various morphological characters (specimens largely agreed with the description provided by Dutta & Manamendra-Arachchi, 1996 and Manamendra-Arachchi & Pethiyagoda, 2006). Specimens were released at the site of capture after conclusive identification. A previous collection of four tadpoles of K. taprobanica was made by Kirtisinghe (1958) in the Western Province. Although the tadpole is thus not unknown to science, the previous description lacks important information and a re-desription is therefore warranted. The following larval redescription of K. taprobanica is based on a single tadpole in Gosner stage 39.